APLIKASI E-ARSIP BERBASIS WEB RESPONSIVE DI PEMERINTAH KABUPATEN MUSIRAWAS - Rusdiyanto Rusdi; Joni Karman (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2021)
Currently Information Technology is developing very fast. The use of computers can help simplify and speed up getting output for a system. Along with the development of this technology and the large number of employee data in the Musi Rawas district government, therefore the Musi Rawas district government developed a Responsive Web-based system, the Musi Rawas district government in managing employee data so far still uses conventional methods, where employee file storage still uses hard copy files so that the data loss rate is still very high, in addition to getting reports you have to recap manually. This E-Archive application was created in order to avoid losing employee data files, simplify archive file management and be able to generate reports quickly